Public funding and enrolment into higher education in Europe - Rudolf Winter-Ebmer; Aniela Wirz (Johannes Kepler University of Linz, Department of Economics, 2002)
In this paper we provide evidence for the impact of public funding on enrolment of students in college. We use a panel for European countries and apply instrumental variables techniques to find that public funding for schooling - regardless at what level - does increase college enrolment alike with an elasticity of about one. A second issue concerns the impact of tuition fees, which are found to reduce college enrolment.
Keywords: I22; I28; 330; College enrolment; public funding; tuition costs; Studium; Bildungsverhalten; Hochschulfinanzierung; Studienfinanzierung; Öffentliche Bildungsausgaben; Schätzung; Westeuropa; USA